Psicopatia corporativa: um estudo sobre gestores no Brasil - Costa, Hilda Pinheiro da (2019)
This thesis sought to understand corporate psychopathy, presenting theoretical and methodological elements for a discussion of the phenomenon, especially among workers who occupy management positions. Specifically, we sought to verify the contribution of personality and leadership styles to explain psychopathy in the context of organizations, presenting an integrative model. In this sense, a theoretical section and three empirical studies were carried out. Study 1 aimed to adapt to the Brazilian context a self-report psychopathy instrument, the Self-Report Psychopathy Scale (SRP). 218 people from the general population with an average age of 36 years (SD = 11.5) participated. They also responded to a “normal” personality questionnaire based on the Big Five Factor theory (IGFP-5) and the Dark Triad Dirty Dozen (DTDD), as well as sociodemographic questions. The results showed satisfactory factorial validity and internal consistency, suggesting a shorter scale, then called SRP-BR. In contrast, Study 2 aimed to develop a hetero-reporting instrument for assessing corporate psychopathy in managers (Corporate Psychopathy Perception Scale – EPPC). For this purpose, 330 workers from Fortaleza-CE with an average age of 33 years (SD = 12.4) participated, evaluating their immediate bosses. Overall, the results attested to the pertinence of using the measure, which met the criteria of validity, internal consistency and parsimony. Finally, Study 3 tested the main hypotheses and questions of this dissertation, providing the first approaches for the development of a theoretical model involving personality traits, psychopathy and leadership style. 246 workers participated, considering equally, but independently, managers and subordinates from different organizations in the state of Ceará. The first group, with mean age of 40 years (SD = 10.5), responded to self-report instruments, while the subordinates (mean age 32 years; SD = 8.9) evaluated their managers using hetero-reporting tools. Most hypotheses were confirmed, allowing the proposition of an explanatory model. In both samples, the analyses showed a better fit for a structure in which dark personality correlates with corporate psychopathy, which in turn negatively correlates with transformational leadership style. In conclusion, it is believed that the objectives of this dissertation were achieved, endorsing reflections that allow to identify factors that inhibit and favor the expression of corporate psychopathy. At the same time, possible limitations are acknowledged and some possibilities for future studies that contribute to this area of interest are proposed.